(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The aim of the the present study was to investigate the analgesic activity of methanolic extract of Arisaema tortuosum (MEAT) using acetic acid-induced writhing and hot plate methods. The hot plate method is useful in elucidating centrally mediated antinociceptive responses, while acetic acid-induced writhing is the chemically induced pain of peripheral origin. The MEAT was used at doses of 50, 100, 200 and 400 mg/kg body weight on swiss albino mice. The percentage inhibition of the abdominal constriction reflex increased dose dependently in case of acetic acid-induced pain and in the hot plate method model the extract at the dose of 400 mg/kg significantly increased the pain reaction time (PRT). These studies conclude that A. tortuosum (Wall.) Schott. tuber possesses analgesic activity in a dose dependent manner. In case of acetic acid-induced pain, the extract at the dose of 400 mg/kg body wt. showed 41.19% inhibition of writhing reflex. In case of hot plate method, after 60 minutes the PRT increased to 7.47 ± 0.05 seconds for the extract at the dose of 400 mg/kg body wt. Dhaka Univ. J. Pharm. Sci. 17(1): 37-41, 2018 (June)